Energy efficiency at sea: Knowledge, communication, and situational awareness at offshore oil supply and wind turbine vessels. (October 2018) - Rasmussen, Hanna Barbara; Lützen, Marie; Jensen, Signe
Abstract: The increasing focus on energy efficient operation of vessels can be seen in both legislation and research. This paper focuses attention on the human factor influencing energy efficiency and explores the conditions for improving energy efficiency in working vessels taking situational awareness (SA) theory into consideration. The study builds on two cases: an offshore supply vessel for the oil & gas industry and an installation vessel for wind turbines. The study used qualitative methods based on 49 interviews with seafarers and onshore employees from the vessels and shipping companies. The study has identified that the energy efficiency of a ship is mainly influenced by legislation and the praxis formed on board. The results showed that the theory on SA is very a useful tool in explaining the factors affecting the energy efficiency of a vessel and the praxis. The study has shown that obtaining a more energy efficient operation is complex and depends not only on the officer on board the ship. The improvement of energy efficiency is possible, but there is a need to understand the complexity of the issue and to involve both the crew and the entire system around the ship, and to obtain a shared perspective of energy efficient operation. Furthermore, in order to improve energy efficiency in shipping companies, there is a need to support the seafarers in gaining more skills for operating the ship more energy efficiently; to do this the right way there is a need to create an understanding of the system by the authorities, ship owners and charterers.